(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
Intellectual Property Rights in general refers to the set of intangible assets including invention, creation, and contribution to the contemporaneous field of knowledge which is owned and legally protected by an individual or company from the outside use or implementation without approved consent. The economic growth, financial incentive and motivation for advanced innovations imbedded in the balanced legal protection of Intellectual Property Rights entails proficient, directed and timely updated guidance in the field of Intellectual Property Rights. Intellectual property has increasingly assumed a vital role with the rapid pace of technological, scientific and medical innovation that we are witnessing today. Moreover, changes in the global economic environment have influenced the development of business models where intellectual property is a central element establishing value and potential growth. In India several new legislations for the protection of intellectual property rights (IPRs) have been passed to meet the international obligations under the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). Intellectual property has therefore grown into one of the world’s biggest and fastest-growing fields of law thereby necessitating the demand for IP professionals well versed in this area to deal with (IPRs) across the national and international borders.